Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Question 12 of 25

If [tex]\( f(x) = 3^x + 10 \)[/tex] and [tex]\( g(x) = 2x - 4 \)[/tex], find [tex]\((f+g)(x)\)[/tex].

A. [tex]\( (f+g)(x) = 3^x + 2x + 6 \)[/tex]

B. [tex]\( (f+g)(x) = -3^x - 2x - 14 \)[/tex]

C. [tex]\( (f+g)(x) = 3^x - 2x + 14 \)[/tex]

D. [tex]\( (f+g)(x) = 5x + 6 \)[/tex]


Sagot :

To find [tex]\((f+g)(x)\)[/tex] given the functions [tex]\(f(x) = 3^x + 10\)[/tex] and [tex]\(g(x) = 2x - 4\)[/tex], we need to add these functions together. Let's proceed with the step-by-step solution.

Step 1: Write down the expressions for [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex].

[tex]\[ f(x) = 3^x + 10 \][/tex]
[tex]\[ g(x) = 2x - 4 \][/tex]

Step 2: Add [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex] to find [tex]\((f+g)(x)\)[/tex].

[tex]\[ (f+g)(x) = f(x) + g(x) \][/tex]

Step 3: Substitute the expressions for [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex].

[tex]\[ (f+g)(x) = (3^x + 10) + (2x - 4) \][/tex]

Step 4: Combine like terms.

[tex]\[ (f+g)(x) = 3^x + 10 + 2x - 4 \][/tex]

[tex]\[ (f+g)(x) = 3^x + 2x + 6 \][/tex]

Therefore, the function [tex]\((f+g)(x)\)[/tex] simplifies to:

[tex]\[ (f+g)(x) = 3^x + 2x + 6 \][/tex]

So, the correct answer is:

A. [tex]\((f+g)(x) = 3^x + 2x + 6\)[/tex].
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.